1991
DOI: 10.1093/infdis/163.5.1157
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nonsusceptibihty to Diethylcarbamazine in Wucheria bancrofti

Abstract: This study assessed Wuchereria bancrofti-infected patients who received diethylcarbamazine (DEC) to determined if drug levels were comparable between individuals who continued to harbor circulating microfilariae and those whose blood became clear of parasites, between those with high and low microfilaria counts, and between infected and noninfected persons. Haitian volunteers undergoing treatment for W. bancrofti and two nonendemic controls were enrolled. DEC levels in serum and urine samples were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…drug resistance ͉ helminth parasites ͉ Onchocerca volvulus ͉ overdispersion T he recent dramatic increase in the use of mass drug administration for the control of helminth infections in humans has raised the possibility that anthelmintic drug resistance may impede the success of such control programs. Anthelmintic resistance is already a major problem in veterinary parasitic nematodes (1), and suboptimal responses to treatment have been reported in a number of human helminthiases (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…drug resistance ͉ helminth parasites ͉ Onchocerca volvulus ͉ overdispersion T he recent dramatic increase in the use of mass drug administration for the control of helminth infections in humans has raised the possibility that anthelmintic drug resistance may impede the success of such control programs. Anthelmintic resistance is already a major problem in veterinary parasitic nematodes (1), and suboptimal responses to treatment have been reported in a number of human helminthiases (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…36 If true, it is possible that in children, W. bancrofti are more accessible to the adulticidal mechanisms triggered by DEC. Alternatively, children and adults may have different proportions of susceptible and non-susceptible adult worm populations. 37,38 DEC-fortified salt appeared to affect intestinal parasite infection prevalence and intensity. It should be noted that in this setting, we have observed that helminth infection prevalence and intensity may vary seasonally.…”
Section: Discussionmentioning
confidence: 95%
“…Persistence of LF microfilaraemia has been reported in Haiti after DEC treatment [124], [125]. More recently, a sharp decline in all therapeutic indices with the mf count returning to pre-treatment levels by the fourth year of single annual DEC therapy was reported [126].…”
Section: Monitoring and Evaluationmentioning
confidence: 99%